2022
DOI: 10.1051/sicotj/2022049
|View full text |Cite
|
Sign up to set email alerts
|

Acetabular revision using trabecular titanium (Delta TT) revision cups: A retrospective case series

Abstract: Background: The annual rate of primary THA has been increasing with new designs promoting THA in the younger population, therefore increasing rates and complexity of hip revision surgeries. Different types of acetabular defects in hip revisions, usually make the use of primary cementless cups quite difficult. In complex defects, using cages with cemented cups or combining cementless cups with metal augments, are possible reconstruction solutions. The Delta TT acetabular revision system provides a solution to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…In two cases, the type of reoperation was not specified ( 22 ). Three studies reported no reoperation due to aseptic loosening in their case series ( 20 , 24 , 26 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In two cases, the type of reoperation was not specified ( 22 ). Three studies reported no reoperation due to aseptic loosening in their case series ( 20 , 24 , 26 ).…”
Section: Resultsmentioning
confidence: 99%
“…The general characteristics of the included studies are reported in Table 1 . Three studies included patients that underwent surgery with only Delta TT revision cups for severe acetabular defects ( 20 , 21 , 24 ). In comparison, the other five studies reported results of both Delta TT one and Delta TT revision cups in moderate and severe revision ( 19 , 22 , 23 , 25 , 26 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations